Copper / titanium / TEOS (tetraethyl orthosilicate) rate selective control CMP (chemical mechanical polishing) solution based on TSV (through silicon via)
By using TT-LYK and OHA as inhibitors in the production process of MEMS devices, combined with potassium citrate and DTPMP as complexing agents and surfactants, a CMP polishing liquid for controlling copper/titanium/TEOS rate selectivity was prepared, which solved the problem of the removal rate and surface quality in the prior art, and achieved an efficient and reliable polishing effect.
Patent Information
- Application Number
- CN202411919270.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to effectively control the rate selectivity between copper/titanium/TEOS during the production process of MEMS devices, resulting in the inability to take into account the removal rate and surface quality, and cannot meet the production requirements of semiconductor devices.
A TSV-based CMP polishing solution with selective control of copper/titanium/TEOS rate based on TSV was prepared.
It achieves a high polishing rate and good surface quality, while effectively controlling the rate selectivity between copper/titanium/TEOS, reducing the surface roughness and dielectric layer erosion after polishing, and significantly improving the wafer yield.
Smart Images

Figure CN119709023A_ABST
Abstract
Description
Technical field:
[0001] The invention relates to an alkaline polishing liquid used in the field of chip manufacturing and a preparation method thereof, in particular to an alkaline polishing liquid used for TSV copper / titanium / TEOS rate selectivity control and a preparation method thereof. Background technology:
[0002] Micro-Electro Mechanical System (MEMS) refers to high-precision sensor devices with a size of several millimeters or less, and its internal structure is usually at the micron or even nanometer level. By miniaturizing the mechanical components of traditional sensors and fixing them on silicon wafers with the help of three-dimensional stacking technology (such as three-dimensional silicon through-hole TSV technology), special packaging forms required for various applications are formed, and finally functional integration is achieved through cutting and assembly. Compared with traditional wire bonding packaging technology, the interconnection packaging technology based on silicon through-holes not only effectively reduces the size of MEMS devices, but also improves their integration.
[0003] In the production process of MEMS devices, the chemical mechanical polishing (CMP) process for copper / titanium / TEOS requires the polishing liquid to have a high removal rate and good surface quality, while being able to effectively control the interface corrosion between copper and titanium. At present, the mainstream TSV copper / titanium / TEOS CMP polishing liquid in the industry is mainly composed of nano-silicon dioxide, oxidants, chelating agents, inhibitors and surfactants. The combination and optimization of these ingredients are crucial to improving process efficiency and device performance.
[0004] CN114106704A discloses a chemical mechanical polishing liquid, which contains silicon dioxide abrasive particles, potassium citrate, potassium tartrate or glycine as a complexing agent, nicotinic acid as an inhibitor and pH regulator, and the carboxyl group (-COOH) in the molecular structure of nicotinic acid can form a coordination bond with the titanium surface, blocking the corrosion process by adsorption film formation to achieve corrosion inhibition. This polishing liquid can only inhibit the corrosion and scratching of the titanium metal surface, and cannot take into account the removal rate and surface quality, and thus cannot meet the production requirements of semiconductor devices. Other related reports such as CN114958206A and CN111378378A are also only aimed at improving the removal rate of copper or only focus on the surface roughness of copper during the polishing process. During the barrier layer polishing process, the rate selectivity control between copper / titanium / TEOS will directly affect the surface quality after polishing, which is directly related to the stability of the device. Summary of the invention:
[0005] The purpose of the present invention is to provide a TSV-based CMP polishing liquid for selectively controlling the rate of copper / titanium / TEOS in view of the limitations of the special polishing liquid for selectively controlling the rate of copper / titanium / TEOS in the current technology. The polishing liquid adopts 2,2'-[[((methyl-1H-benzotriazole-1-yl)methyl]imino]diethanol (TT-LYK) and octyl hydroxamic acid (OHA) as inhibitors to act alone or in combination, and under the synergistic effect of a complexing agent, the polishing liquid has a high polishing rate and good surface quality. At the same time, the selective control of the rate between copper / titanium / TEOS can be controlled, and the dish-shaped depression and dielectric layer erosion after polishing are improved. The preparation process of the polishing liquid obtained by the present invention is simple, easy to mass produce, and meets the actual needs of industrial applications.
[0006] In order to solve the above technical problems, the technical solution of the present invention is:
[0007] A TSV-based copper / titanium / TEOS rate selectively controlled CMP polishing liquid, the composition of the polishing liquid and the mass ratio of the polishing liquid include the following:
[0008] Nano silicon dioxide 3.00-10.00wt%
[0009]
[0010] The pH value of the alkaline polishing liquid is 8.0;
[0011] The complexing agent is potassium citrate (KCit) and diethylenetriamine penta (methylenephosphonic acid) (DTPMP);
[0012] The inhibitor is one or both of 2,2'-[[((methyl-1H-benzotriazol-1-yl)methyl]imino]bisethanol (TT-LYK) and octyl hydroxamic acid (OHA);
[0013] The surfactants are ammonium dodecyl sulfate (ADS) and isomeric decanol polyoxyethylene ether (JFC-E);
[0014] The oxidant is hydrogen peroxide (H2O2);
[0015] The average particle size of the nano silicon dioxide is 60-70 nanometers, and the dispersion is maintained within ±5%.
[0016] The method for preparing the TSV-based copper / titanium / TEOS rate selectively controlled CMP polishing liquid comprises the following steps:
[0017] The alkaline and acidic compounds are dissolved in water to prepare acid and base regulators, respectively, and the complexing agent, inhibitor, surfactant, nano-silicon dioxide and oxidant are added to deionized water according to the ratio, and the acid-base regulator is added dropwise to the solution by titration to adjust the pH value of the solution to 8.0; and the solution is stirred under vacuum negative pressure, the stirring speed is controlled at 60-80 rpm, the stirring time is 2-15 minutes, and the temperature is maintained at 15-25° C. After the stirring is completed, ultrafiltration is first performed using a 600 nm pore size filter element, and then ultrafiltration is performed using a 300 nm pore size filter element;
[0018] The alkaline compound is any one of potassium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, polyaspartic acid and ammonia water;
[0019] The acidic compound is nitric acid.
[0020] The essential features of the present invention are:
[0021] The complexing agent diethylenetriamine penta (methylenephosphonic acid) (DTPMP) used in the present invention has oxygen atoms in the phosphate group in its structure that can react with Cu and Ti ions; potassium citrate (KCit) reacts with the Cu and Ti surfaces through the carboxylic acid group in its structure, thereby increasing the reaction rate during the polishing process. 2,2'-[[((Methyl-1H-benzotriazol-1-yl)methyl]imino]diethanol (TT-LYK) is an azole inhibitor that uses the nitrogen-nitrogen double bond in its molecular structure to react with the Cu and Ti surfaces to form a molecular adsorption film to achieve corrosion inhibition; octyl isohydroxamic acid (OHA) uses the oxime group in its molecular structure to react with the Cu and Ti surfaces to form a passivation film mainly based on ionic adsorption to achieve corrosion inhibition; the two can act alone or in combination to simultaneously inhibit the chemical corrosion of Cu and Ti, and can effectively protect TEOS significantly improves the surface quality after polishing. During the polishing process, the addition of surfactant (JFC-E) can maintain the stable dispersion state of abrasive ions in the polishing liquid and prevent the occurrence of agglomeration, thereby ensuring the consistency and reliability of the entire polishing process. In addition, its good wetting properties can make the polishing liquid spread quickly on the wafer surface, reduce surface tension, and help further improve polishing quality and efficiency; the various components in the polishing liquid work together to achieve a polishing rate of Cu:Ti:TEOS approximately 1:1:1, meeting the technical requirements for barrier layer polishing.
[0022] The beneficial effects of the present invention are as follows:
[0023] The present invention has a good selective removal rate: after polishing, the removal rate selection ratio of copper / titanium / TEOS is close to 1:1:1, which meets the process requirements and ensures production efficiency. In addition, the polishing liquid can significantly inhibit the interface corrosion between copper and titanium, and effectively reduce the roughness of the surface after polishing, which significantly improves the yield rate of the wafer surface. At the same time, the inhibitor is easy to remove, which provides great convenience for the subsequent cleaning process.
[0024] It also has excellent pH characteristics: the polishing liquid is weakly alkaline with a pH value of 8.0, which is less corrosive to the polishing equipment than acidic polishing agents, helping to extend the service life of the equipment.
[0025] In summary, the polishing liquid of the present invention has excellent performance and good economy, and provides an efficient and reliable solution for the semiconductor manufacturing industry. Description of the drawings:
[0026] Figure 1 , Surface roughness image of Cu after chemical mechanical polishing in Example 1;
[0027] Figure 2 , Surface roughness image of Ti after chemical mechanical polishing in Example 1;
[0028] Figure 3 , Surface roughness image of TEOS after chemical mechanical polishing in Example 1;
[0029] Figure 4 , Surface roughness image of Cu after chemical mechanical polishing in Example 2;
[0030] Figure 5 , Example 2Ti, surface roughness map after chemical mechanical polishing;
[0031] Figure 6 , Surface roughness image after TEOS chemical mechanical polishing in Example 2;
[0032] Figure 7 , Surface roughness image of Cu after chemical mechanical polishing in Example 3;
[0033] Figure 8 , Surface roughness image of Ti after chemical mechanical polishing in Example 3;
[0034] Fig. 9 , Surface roughness image after TEOS chemical mechanical polishing in Example 3;
[0035] Fig.10 , Surface roughness image of Cu after chemical mechanical polishing in Example 4;
[0036] Fig.11 , Surface roughness image of Ti after chemical mechanical polishing in Example 4;
[0037] Fig.12 , Surface roughness image of TEOS after chemical mechanical polishing in Example 4;
[0038] Fig.13 , Surface roughness image of Cu after chemical mechanical polishing in Example 5;
[0039] Fig.14 , Surface roughness image of Ti after chemical mechanical polishing in Example 5;
[0040] Fig.15 , Surface roughness image after TEOS chemical mechanical polishing in Example 5;
[0041] Fig.16 , Surface roughness image of Cu after chemical mechanical polishing in Example 6;
[0042] Fig.17 , Surface roughness image of Ti after chemical mechanical polishing in Example 6;
[0043] Fig.18 , Surface roughness image after TEOS chemical mechanical polishing in Example 6;
[0044] Fig.19 , Surface roughness image of Cu after chemical mechanical polishing in Example 7;
[0045] Fig. 20 , Surface roughness image of Ti after chemical mechanical polishing of Example 7;
[0046] Fig.21 , Surface roughness image after TEOS chemical mechanical polishing in Example 7; Specific implementation method:
[0047] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the best embodiment.
[0048] Embodiment 1:
[0049] Polishing process conditions: On an RX-500 polishing machine, a copper sheet with a diameter of 3 inches and a thickness of 2 mm (purity of 99.99%) and a titanium sheet with a diameter of 3 inches and a thickness of 2 mm (purity of 99.99%) were polished, with an operating pressure of 1.5 psi, a disc speed of 93 rpm, a polishing head speed of 87 rpm, and a polishing liquid flow rate of 240 ml / min; a 4-inch TEOS-coated sheet was polished on a Huahai Qingke U300B polishing machine, with an operating pressure of 1.5 psi, a disc speed of 93 rpm, a polishing head speed of 87 rpm, and a polishing liquid flow rate of 240 ml / min.
[0050] Polishing test conditions: A four-probe tester (Four Dimensions, Inc, 333A) was used to measure the change in the amount of metal film removed before and after CMP treatment to calculate the removal rate of the target material. The difference in thickness of the TEOS film before and after polishing was measured by a dielectric film thickness gauge (Filmetrics, Inc, F50-UV), and the TEOS removal rate was obtained. An atomic force microscope (AFM) 5600LS produced by Agilent was used to measure the morphology and roughness of the wafer surface. A high-precision analytical balance (Mettler Toledo AB204-N, accuracy of 0.1 mg) was used to weigh the reagents.
[0051] Prepare 3L polishing liquid:
[0052] 1. Take 30g of potassium citrate (accounting for 1wt% of the total polishing liquid, purity is 99.8%) and 1.5g of TT-LYK (500ppm, 99.8%), add them into 50mL of deionized water respectively, stir until dissolved to form a dilute solution.
[0053] 2. Take 375 mL of abrasive silica sol (the main component is nano-silicon dioxide, with an average particle size of 60-70 nm, a purity of 40%, and a dispersion between ±5%), add it to 2 times of deionized water, stir it, and form a dilute solution of silica sol.
[0054] 3. Add the diluted component solutions and 80 mL of 30% by mass aqueous hydrogen peroxide solution (accounting for 0.8 wt % of the total polishing solution) to the diluted aqueous solution of silica sol in sequence, stirring evenly while adding.
[0055] 4. Using titration method, add the prepared acid-base regulator (30% nitric acid and 30% potassium hydroxide solution, respectively) to the above solution, adjust the pH value of the prepared solution to 8, and stir under vacuum negative pressure conditions, the stirring speed is controlled at 60-80r / min, the stirring time is 2-15min, and the temperature is maintained at 15-25°C. After stirring, first use a 600nm pore size filter element for ultrafiltration, and then use a 300nm pore size filter element for ultrafiltration.
[0056] Embodiment 2-6:
[0057] The other steps are the same as those in Example 1, and the changes in the contents of the relevant materials are shown in Table 1.
[0058] Table 1 Polishing liquid formula of Examples 1-6
[0059]
[0060] Table 2 Effect data of Examples 1-6
[0061]
[0062]
[0063] According to Table 2 and Figure 1-Figure 21 The data show that the removal rate selectivity ratio of copper / titanium / TEOS in this study is about 1:1:1. In the TSV barrier layer polishing, the removal rate of Ti is slightly higher than that of Cu, which can effectively prevent the problem of dishing pits during polishing and improve the surface quality.
[0064] Comparing Examples 1 and 4, 2 and 6, the results show that adding surfactants during polishing can not only improve mass transfer efficiency and wafer flatness, but also reduce the surface tension of the polishing liquid to improve surface quality. Comparing Experiments 1 and 5, the results show that increasing the abrasive concentration in the polishing liquid can significantly increase the polishing rate. At this time, the removal rates of copper and titanium are both increased to The above, but also increased the possibility of surface scratches, increased surface roughness. Comparing Examples 2, 3 and 4, after the inhibitor OHA and TT-LYK were compounded, the removal rate, static corrosion rate and surface roughness all decreased to a certain extent compared with adding only one single inhibitor component, which shows that the compounding achieved a better effect.
[0065] The working principle of the alkaline polishing solution for TSV copper / titanium / TEOS rate selectivity control mentioned above:
[0066] Nano-silicon dioxide, as an abrasive, has excellent fluidity and strong dispersibility, can achieve a delicate polishing effect, and is very suitable for processing high-precision surfaces. In addition, its abrasive particles are easy to clean after polishing, reducing the complexity of subsequent cleaning, thereby reducing production costs, making it an ideal abrasive choice.
[0067] Potassium citrate, as a green and environmentally friendly organic chelating agent, can effectively form complexes with metal ions, prevent the precipitation or solidification of metal ions during the polishing process, and ensure the stability of the polishing agent. It is environmentally friendly and multifunctional. It can not only be used as a chelating agent, but also as a buffer to help maintain the pH value of the polishing liquid, thereby further improving the stability of the polishing liquid. DTPMP is an organic phosphoric acid reagent. Many scholars have studied the chelating ability of DTPMP for heavy metals and used DTPMP to remove heavy metals such as calcium and lead from industrial water. In oil production, DTPMP can be used as a scale inhibitor to chelate Ca ions to inhibit the formation of calcium carbonate and increase oil production. In this study, DTPMP can effectively chelate metal ions and increase the polishing rate.
[0068] As an inhibitor, TT-LYK eliminates potential high and low differences, ensuring more uniform material removal and high surface smoothness during the polishing process; while OHA can simultaneously inhibit the corrosion of copper and titanium and effectively protect the low-K dielectric layer. The two can achieve good results on the polished surface when used alone or in combination. Hydrogen peroxide (H2O2) as an oxidant has the advantages of being environmentally friendly, pollution-free and inexpensive, making it very suitable for industrial production. As a surfactant, isomeric decanol polyoxyethylene ether (JFC-E) can reduce surface damage by reducing surface tension and reducing the surface mechanical stress of the polishing liquid on the wafer. It also has a certain emulsifying function, which can effectively disperse abrasive particles and improve the mass transfer efficiency during polishing.
[0069] The above-mentioned reference to a specific embodiment of an alkaline polishing solution for selective control of TSV copper / titanium / TEOS rate and a preparation method thereof are described in detail, which is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.
[0070] Matters not covered by the present invention are known technologies.
Claims
1. A TSV-based copper / titanium / TEOS rate selectively controlled CMP polishing liquid, characterized by: The composition of the polishing liquid and the mass ratio of the polishing liquid include the following: The pH value of the alkaline polishing liquid is 8.0; The inhibitor is one or both of 2,2'-[[((methyl-1H-benzotriazol-1-yl)methyl]imino]bisethanol (TT-LYK) and octyl hydroxamic acid (OHA).
2. The TSV-based copper / titanium / TEOS rate selectively controlled CMP polishing liquid according to claim 1, characterized in that: The complexing agent is potassium citrate (KCit) and diethylenetriamine penta (methylenephosphonic acid) (DTPMP).
3. The TSV-based copper / titanium / TEOS rate selectively controlled CMP polishing liquid according to claim 1, characterized in that: The surfactants are ammonium dodecyl sulfate (ADS) and isomeric decanol polyoxyethylene ether (JFC-E).
4. The TSV-based copper / titanium / TEOS rate selectively controlled CMP polishing liquid according to claim 1, characterized in that: The nano silicon dioxide has an average particle size of 60-70 nanometers, and the dispersion is maintained within ±5%.
5. The TSV-based copper / titanium / TEOS rate selectively controlled CMP polishing liquid according to claim 1, characterized in that: The oxidant is hydrogen peroxide (H2O2).
6. The method for preparing a TSV-based copper / titanium / TEOS rate selectively controlled CMP polishing liquid according to claim 1, characterized in that The steps include: The alkaline and acidic compounds are dissolved in water to prepare acid and alkaline regulators respectively; the complexing agent, inhibitor, surfactant, nano-silica and oxidant are added to deionized water according to the proportion, and stirred under vacuum negative pressure conditions, the stirring speed is controlled at 60-80 rpm, the stirring time is 2-15 minutes, and the temperature is maintained at 15-25° C. After the stirring is completed, ultrafiltration is first performed using a 600nm pore size filter element, and then ultrafiltration is performed using a 300nm pore size filter element; and the alkaline compound and the acidic compound are used as regulators and added dropwise to the solution by titration to adjust the solution to the target pH value; The alkaline compound is any one of potassium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, polyaspartic acid and ammonia water; The acidic compound is nitric acid.
Citation Information
Patent Citations
Chemical mechanical polishing solution and application thereof
CN111378378A
Copper chemical mechanical polishing solution, application thereof and chemical mechanical polishing method
CN114958206A
Polishing solution for reducing surface defects in multilayer cobalt interconnection barrier layer CMP and preparation method thereof
CN110951400A
Control method for CMP rate selectivity of multi-layer copper interconnection barrier layer
CN112355884A
Green and environment-friendly titanium metal polishing solution
CN114106704A
Cited By
Acid polishing solution for dielectric layer as well as preparation method and application of acid polishing solution
CN121851908A
An acidic polishing solution for dielectric layers, its preparation method and use
CN121851908B